Characterization and Application of Natural Photosensitizer and Poly(vinylidene Fluoride) Nanofiber Membranes-Based Electrolytes in DSSC - Zakiyah, Nafisatus; Kusumawati, Nita; Setiarso, Pirim; Muslim, Supari; A'yun, Qurrota; Putri, Marinda Mayliansarisyah (Indonesian Journal of Chemistry, 2024)
This comprehensive research has explored the potential of enhancing dye-sensitized solar cells (DSSC) by harnessing environmentally friendly natural dyes, such as chlorophyll pigments from pandanus (664.1 nm) and papaya leaves (664.0 nm), as well as betacyanin pigments from sappan-mangosteen (536.2 nm). Electrochemical analyses elucidated the energy band gaps, revealing a hierarchy with the smallest band gap observed for papaya leaves (1.387 eV), followed closely by sappan-mangosteen (1.389 eV) and pandan leaves (1.396 eV). This research effectively addressed the persistent issue of electrolyte leakage in DSSC development by introducing a polymer electrolyte derived from polyvinylidene fluoride (PVDF) through electrospinning and phase inversion techniques. SEM characterization results and thermogravimetric analysis underscored the superior characteristics and high thermal stability of the PVDF nanofiber polymer for DSSC applications. The study's pivotal findings underscore the remarkable DSSC performance achieved with chlorophyll pigment from papaya leaves, reaching 1.31% efficiency without a polymer electrolyte. Moreover, the sappan-mangosteen dye emerged as a promising contender with the highest efficiency values when applied with polymer electrolyte, recording rates of 1.17% for PVDF NF and 0.95% for PVDF, which are notably comparable to the efficiency of liquid electrolyte at 1.26%.